Prevalence of anxiety and depressive symptoms among emergency physicians in Libya after civil war: a cross-sectional study. Issue 8 (27th August 2020) - Elhadi, Muhammed; Khaled, Ala; Malek, Ans Bassam; El-Azhari, Ahmed El-Alem; Gwea, Ahmed Zakaria; Zaid, Ahmed; Elturki, Salman Mabruk; Aburgegah, Ahmed; Abu Ageila, Munir Ahmed K; Alhadi, Abdulmueti; Albashkar, Hafed Abdulwahhab; Alshareef, Aliyah Mustafa; et al.
Abstract : Objectives: We aimed to identify the prevalence of depression and anxiety among physicians working in the emergency departments of nine tertiary care centres in Libya. Design: This was a cross-sectional study. Setting: Nine main tertiary centres in Libya Participants: Emergency department doctors were surveyed between December 2018 and February 2019. Intervention: The standardised Hospital Anxiety and Depression Scale (HADS) was selected as a measurement tool for analysing anxiety and depression symptoms; a HADS score of 8 indicated anxiety as well as depression symptoms. The primary outcomes were anxiety and depression, which were tabulated with independent sociodemographic variables. χ 2 tests were conducted to compare the prevalence of anxiety and depression between the groups. Statistical analysis was performed using SPSS V.25. Results: A total of 108 out of 150 (72%) emergency physicians from all levels participated in the study and took the survey. The emergency physicians had a mean±SD age of 31.2±4.5 years, and were predominantly males (74 out of 108, 68.5%). Overall, 49 (45.4%) physicians reached the cut-off score to define both depression and anxiety (ie, a score ≥8). In terms of violence, 71 (65.7%) reported incidents of verbal violence, while 26 (24.1%) reported physical violence or abuse by militias. In addition, 28 reported being threatened by militias. Conclusion: The high prevalence rate of anxiety and depression is of concern, and the high rate of physical and verbal abuse highlights the range of abuse endured by doctors in Libya. Therefore, screening for anxiety and depression at regular intervals is needed to avoid the deterioration of mental health, which can increase the risk of suicide and dropping out, and decrease the level of healthcare for patients.